Epidemiology of Yellow Fever in Nigeria: Analysis of Climatic, Ecological, Socio-Demographic, and Clinical Factors Associated with Viral Positivity Among Suspected Cases Using National Surveillance Data, 2017–2023 - Stephen Eghelakpo Akar; William Nwachukwu; Oludare Sunbo Adewuyi; Anthony Agbakizua Ahumibe; Iniobong Akanimo; Oyeladun Okunromade; Olajumoke Babatunde; Chikwe Ihekweazu; Mami Hitachi; Kentaro Kato; Yuki Takamatsu; Kenji Hirayama; et al. (Journal of Epidemiology and Global Health)
Abstract Background Since its resurgence in 2017, Yellow fever (YF) outbreaks have continued to occur in Nigeria despite routine immunization and the implementation of several reactive mass vaccinations. Nigeria, Africa’s most populous endemic country, is considered a high-priority country for implementing the End Yellow fever Epidemics strategy. Methods This retrospective analysis described the epidemiological profile, trends, and factors associated with Yellow fever viral positivity in Nigeria. We conducted a multivariable binary logistic regression analysis to identify factors associated with YF viral positivity. Results Of 16,777 suspected cases, 8532(50.9%) had laboratory confirmation with an overall positivity rate of 6.9%(585). Predictors of YFV positivity were the Jos Plateau, Derived/Guinea Savanah, and the Freshwater/Lowland rainforest compared to the Sahel/Sudan Savannah; dry season compared to rainy season; the hot dry or humid compared to the temperate, dry cool/humid climatic zone; 2019, 2020, 2021, 2022, and 2023 epidemic years compared to compared to 2017; first, third, and fourth quarters compared to the second; male sex compared to female; age group > = 15 years compared to < 15 years; working in outdoor compared to indoor settings; having traveled within the last two weeks; being of unknown vaccination status compared to being vaccinated; and vomiting. Conclusion Ecological, climatic, and socio-demographic characteristics are drivers of YF outbreaks in Nigeria, and public health interventions need to target these factors to halt local epidemics and reduce the risk of international spread. Inadequate vaccination coverage alone may not account for the recurrent outbreaks of YF in Nigeria.